2017
DOI: 10.1038/srep43736
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Proliferation and Epithelial Mesenchymal Transition in Retinal Pigment Epithelial Cells by Heavy Chain-Hyaluronan/Pentraxin 3

Abstract: Proliferative vitreoretinopathy (PVR) is mediated by proliferation and epithelial mesenchymal transition (EMT) of retinal pigment epithelium (RPE). Because heavy chain-hyaluronic acid/pentraxin 3 (HC-HA/PTX3) purified from human amniotic membrane exerts anti-inflammatory and anti-scarring actions, we hypothesized that HC-HA/PTX3 could inhibit these PVR-related processes in vitro. In this study, we first optimized an ARPE-19 cell culture model to mimic PVR by defining cell density, growth factors, and cultivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 73 publications
0
43
0
Order By: Relevance
“…TGF-β induces EMT of RPE cells via two pathways: the classical SMAD-dependent pathway and the SMAD-independent pathway ( Fig. 2 ) ( Cai et al, 2018 ; He et al, 2017 ; Heffer et al, 2019 ; Ishikawa et al, 2015 ; Takahashi, Haga & Tanihara, 2015 ; Yao et al, 2019 ; Zhang et al, 2017 ; Zhang et al, 2018b ; Zhou et al, 2017 ). In the SMAD dependent pathway, TGF-β binds to cell surface receptor complexes, and activates type I TGF-β receptors, which phosphorylate SMAD2 and SMAD3.…”
Section: Survey Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β induces EMT of RPE cells via two pathways: the classical SMAD-dependent pathway and the SMAD-independent pathway ( Fig. 2 ) ( Cai et al, 2018 ; He et al, 2017 ; Heffer et al, 2019 ; Ishikawa et al, 2015 ; Takahashi, Haga & Tanihara, 2015 ; Yao et al, 2019 ; Zhang et al, 2017 ; Zhang et al, 2018b ; Zhou et al, 2017 ). In the SMAD dependent pathway, TGF-β binds to cell surface receptor complexes, and activates type I TGF-β receptors, which phosphorylate SMAD2 and SMAD3.…”
Section: Survey Methodologymentioning
confidence: 99%
“… Hatanaka et al (2012) reported that PPAR-γ agonist pioglitazone could prevent TGF-β-induced morphological changes and the up-regulation of EMT-related markers in primary monkey RPE cells, through inhibition of the SMAD pathway. Some drugs, including dichloroacetate (DCA) ( Shukal et al, 2020 ), salinomycin (SNC) ( Heffer et al, 2019 ), resveratrol ( Ishikawa et al, 2015 ), protein kinase A inhibitor H89 ( Lyu et al, 2020 ) and heavy chain-hyaluronan/pentraxin3 ( He et al, 2017 ), reportedly inhibit EMT in an in vitro EMT cell model and prevent PVR development by blocking the activation of theTGF-β pathway. Thus, inhibition of EMT by pharmacological agents may be an effective strategy to prevent PVR development.…”
Section: Survey Methodologymentioning
confidence: 99%
“…In the pathogenesis of PVR, another characteristic of PVR is the formation of PVR membranes whose contraction causes a retinal re-detachment [8]. So we attempted to apply a collagen gel contraction assay for mimicking this clinical event to discover drugs that can potentially prevent the pathogenesis of PVR.…”
Section: Cmr Blocks Vitreous-induced Contraction Of Arpe-19mentioning
confidence: 99%
“…Retinal pigment epithelial cells (RPEs) are considered to be important and central players in the pathogenesis of PVR. When the retina is detached by contraction [8], retinal cells (e.g. RPEs) form the epi-or sub-retinal membranes undergoing a series of responses including proliferation and migration [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, a reversal of the trend of rising temperatures from the 1990s might be consistent with the AMO. On the other hand, it is reasonable to suggest that the successive global record setting years since 2014 (NOAA 2017, Gillis 2017, Su et al 2017, Thompson 2017 will be reflected over the next few years in the average annual and monthly changes for Prince Edward Island.…”
Section: Seasonmentioning
confidence: 99%